Madrasa Agility In The Digital Age: Increasing Flexibility And Countering Artificial Intelligence Threats - Sutrisno Sutrisno (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2023)
This study aims to analyze the sustainability of Madrasa in the digital era by focusing on two aspects, namely increasing flexibility and dealing with the threat of artificial intelligence. This research was conducted using the library research method, with data collection techniques in the form of systematic literature reviews. The results of the study show that the sustainability of Madrasa in the digital era is very dependent on the ability of Madrasa to increase flexibility and face the threat of artificial intelligence. Increased flexibility is carried out by developing learning programs that can be accessed online and offline, using innovative learning technology, and involving teachers and students in the learning process. Meanwhile, to deal with the threat of artificial intelligence, Madrasa need to improve digital capabilities and prepare teachers and students to face changes in an increasingly complex and dynamic world of work. Madrasa also need to strengthen Islamic values ​​and wisely introduce artificial intelligence concepts. The sustainability of madrasa in the digital era requires a holistic approach, which includes aspects of technology, management, and curriculum. In the face of artificial intelligence, madrasa need to strengthen their identity and reputation as institutions that provide high quality education and strong Islamic values. Madrasa also need to strengthen Islamic values ​​and wisely introduce artificial intelligence concepts. The sustainability of madrasa in the digital era requires a holistic approach, which includes aspects of technology, management, and curriculum. In the face of artificial intelligence, madrasa need to strengthen their identity and reputation as institutions that provide high quality education and strong Islamic values. Madrasa also need to strengthen Islamic values ​​and wisely introduce artificial intelligence concepts. The sustainability of madrasa in the digital era requires a holistic approach, which includes aspects of technology, management, and curriculum. In the face of artificial intelligence, madrasa need to strengthen their identity and reputation as institutions that provide high quality education and strong Islamic values. Keywords: Madrasa, Agility, Digital, Artificial Intelligence